FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA USAHA PADA NASABAH KUR BRI SEMARANG - Lia Ariani; Ratih Hesty Utami Puspitasari; Qristin Violinda (JURNAL BISNIS KOLEGA, 2023)
This study aims to determine the factors that influence the business performance of BRI KUR customers, Pattimura Branch, Semarang. The sampling technique used was purposive sampling technique, the number of samples taken was 140 respondents. The data analysis method used is multiple linear regression analysis using SPSS version 22. The results of this study indicate that own capital has a positive and significant effect on business performance with a t-count value of (5.694) greater than a t-table value of (1.656) and a significance level of (0.000) is less than the minimum significance level of (0.05). People's business credit capital has a positive and significant effect on business performance with a t-count value of (2.077) greater than the t-table value of (1.656) and a significance level of (0.040) smaller than the minimum significance level of (0.05) . Length of business has a positive and significant effect on business performance with a t-count value of (4.676) greater than the t-table value of (1.656) and a significance level of (0.000) less than the minimum significance level of (0.05).